Flavonoid Concentration and Tyrosinase Inhibition Activity of Ethanol Extract of Piper crocatum (Piper crocatum var. Ruiz & Pav) from Various Regions in Indonesia and Their Correlations - Irsal, Riyan Alifbi Putera; Safithri, Mega; Andrianto, Dimas; Mardliyati, Etik (Jurnal Kimia Valensi, 2023)
Hyperpigmentation is a condition of darkening of the skin which is generally caused by an increase in melanin production. Melanin is produced in melanocytes by the enzyme tyrosinase. Piper crocatum contains flavonoid compounds that are known from previous research to inhibit tyrosinase. The goals of this study were to determine the tyrosinase inhibitory activity and total flavonoid content of seven accessions, as well as look at the Pearson’s correlation and clustering PCA (principal component analysis). The method used was water content analysis, extraction yield measurement, total flavonoids analysis, and in vitro tyrosinase inhibition. Based on the results, P. crocatum from Kendari had the best yield and total flavonoid content of 24.07% and 5.10 mg QE g-1, while P. crocatum from Bogor had the lowest water content with a value of 6.21% and the best in tyrosinase inhibition of 13.77. The correlation between total flavonoid content and percent inhibition showed a very weak correlation. The results of clustering formed four clusters of seven accessions based on total flavonoids and percent inhibition. The cluster was divided into Malang (506mDPL) and Jayapura (287mDPL), Banda Aceh (0.80mDPL) and Bandung (670mDPL), Samarinda (8mDPL) and Bogor (190-350m DPL), and Kendari (14mDPL). In conclusion, the correlation between total flavonoid levels and percent inhibition is very weak and regional diversity had a significant effect on total flavonoids and total inhibition.